2011
DOI: 10.1007/s12192-010-0243-5
|View full text |Cite
|
Sign up to set email alerts
|

Functional switching of a novel prokaryotic 2-Cys peroxiredoxin (PpPrx) under oxidative stress

Abstract: Many proteins have been isolated from eukaryotes as redox-sensitive proteins, but whether these proteins are present in prokaryotes is not clear. Redox-sensitive proteins contain disulfide bonds, and their enzymatic activity is modulated by redox in vivo. In the present study, we used thiol affinity purification and mass spectrometry to isolate and identify 19 disulfide-bond-containing proteins in Pseudomonas putida exposed to potential oxidative damages. Among these proteins, we found that a typical 2-Cys Prx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…While this chaperone activity has mostly been associated with eukaryotic peroxiredoxins, it was shown that AhpC (a nonclassical Ahp) from Helicobacter pylori acts as a molecular chaperone under conditions of oxidative stress (69). Peroxiredoxins from Pseudomonas putida and P. aeruginosa were also shown to have chaperone activity (70)(71)(72). Consistent with this hypothesis, it was recently found that B. subtilis AhpA is inactivated in vitro when exposed to moderately high levels of H 2 O 2 (293 M); AhpC was unaffected by this level of peroxide (29).…”
Section: Discussionmentioning
confidence: 99%
“…While this chaperone activity has mostly been associated with eukaryotic peroxiredoxins, it was shown that AhpC (a nonclassical Ahp) from Helicobacter pylori acts as a molecular chaperone under conditions of oxidative stress (69). Peroxiredoxins from Pseudomonas putida and P. aeruginosa were also shown to have chaperone activity (70)(71)(72). Consistent with this hypothesis, it was recently found that B. subtilis AhpA is inactivated in vitro when exposed to moderately high levels of H 2 O 2 (293 M); AhpC was unaffected by this level of peroxide (29).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the enzymatic analysis results, this PpPrx has dual functions as a dominant chaperone and a recessive peroxidase activity (An et al, 2011). The PaPrx protein from P. aeruginosa PAO1 also contains 200 amino acids, and has dual functions as a dominant peroxidase and a recessive chaperone (An et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Oxidized Cys P is attacked by the resolving Cys (Cys R ). Two oxidized active Cys residues are formed via intra-or intermolecular disulfide bonds after yielding water or the corresponding alcohol (An et al, 2010;2011;Dietz, 2003;Hofmann et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oligomerization state of Ino‐1 was analyzed using the method previously described (An et al., ). The mixtures of the purified Ino‐1 and the loading buffer [250 mM Tris‐HCl (pH 6.8), 0.5% bromophenol blue (BPB), and 50% (v/v) glycerol] were separated on 12% PAGE and stained with Coomassie Brilliant Blue or detected by western blotting with anti‐his antibody.…”
Section: Methodsmentioning
confidence: 99%